Peran Negara Donor dan Organisasi Internasional Melalui InaTEWS dalam Disaster Risk Reduction di Indonesia - Hapsari, Dorothea Ratri Parama; Farabi, Nadia (Journal of International Relations, 2020)
This study discusses the role of donor countries and international organizations through InaTEWS (Indonesia Tsunami Early Warning System) in Disaster Risk Reduction to fulfill the economic security of the Indonesian people. InaTEWS is a tsunami early warning system in Indonesia, which is expected to reduce the risk of tsunamis, for the sake of achieving human security. The huge losses in the 2004 tsunami tragedy that struck Aceh and neighboring countries became a starting point for supporting the development of a tsunami in the Indian Ocean region. Germany and various donor countries and other international organizations provide development assistance and development for InaTEWS. This research uses the concept of human security to explain the basic human needs of "freedom from fear" and "freedom from desire" specifically for economic security. In addition, related to the concept of disaster, the disaster risk management cycle (Disaster Risk Management) as a Disaster Risk Reduction strategy (Disaster Risk Reduction Framework) and the Hyogo Framework for Action 2005-2015 as an international guideline for disaster risk solutions. The results of this study show how the role of donor countries and international organizations through InaTEWS in Disaster Risk Reduction to meet the economic security of the Indonesian people who implemented the 2005- 2015 HFA through InaTEWS in the mitigation phase needed to carry out Disaster Risk Reduction to obtain economic security.